Safety Attitude in Operating Room's Staff's in selected hospitals of Tehran University of Medical Sciences in 2013 - Mohammad Arab; Farugh Mohammadian; Abdolrasoul Rahmani; Abbas Rahimi; Leyla Omidi; Parvin abbasi brojeni; Mehdi Asghari (Tehran University of Medical Sciences, 2014)
Background and Objective: The operating room is one of the main units in hospital, where the most important phase of patient treatment is performed. This study aimed to investigate the safety attitude among the staff of operating room in selected hospitals of Tehran University of Medical Sciences.Methods: In this descriptive - analytical study, 230 staff of operating room of hospitals affiliated to Tehran University of medical sciences were selected by Random cluster sampling. Research tool was a safety attitude questionnaire (Cronbach's alpha 0.854) that classified in 3 categories: demographic questions (11questions), quality of communications (14questions) and safety attitude questions (58 questions). All data collected were analyzed using SPSS18. T-test, Spearman correlation, analysis of variance (ANOVA) and Chi-square have been used for data analyzing.Results: The results indicated that 90.9% of staffs had moderate safety attitude and the average of the safety attitude score was 188.52(± 22.4). As the results showed, there was a positive and significant relationship between the safety attitude score and age, total work experience and work experience at hospital (p 046/0=, r =±0.141). There were significant differences between: average of the safety attitude score among men and women (P=0.047) average of the safety attitude score among staffs who have been trained and untrained safety (P=0.004).Conclusion: The safety attitude score among the staff. It is therefore necessary to implement the effective interventions to improve safety attitude among operating room staff in understudy hospitals. Keywords: Safety attitude, Operating Room, Hospital, Staff